Thieves' Latin : poems - Shippy, Peter Jay, 1961- (Iowa poetry prize., 2003)
"Ah, writ happens." Like the con men who rely on thieves' Latin to ply their trade, the poems in Peter Jay Shippy's award-winning collection don't play well with other poems. They are difficult. They rave. They are unsettling and blunt. They crash cars and ride tsunamis and hitch rides on tugs. They also provide a contemporary, ironic, and tender view of America, all the while layering wordplay, cleverness, and sentiment